Differentiation of animal oils by means of gas chromatography mass spectrometry and principle component analysis for halal validation and authentication / Dzulkifly Mat Hashim, Mohammad Nazrim Marikkar and Nina Naquiah Ahmad Nizar - Mat Hashim, Dzulkifly; Marikkar, Mohammad Nazrim; Ahmad Nizar, Nina Naquiah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
In view of the religious restrictions and risks associated with consumption of lard, a proper basis for lard detection has become essential to establish the distinguishable characteristics of lard from other common animal fats. Hence, high demand occurred for rapid and reliable techniques in differentiation and classification of animal fats. The goal of the innovation is to compare lard with other animal fats in terms of their compositional characteristics by GCMS, followed by Principle Component Analysis for authentication of adulterated food products specifically, as a basis to detect lard in animal fats for Halal validation purposes. This method could be used in the industry which needs fast results in determination of animal oil origins by the fatty acid distribution. The simple technique of methylation process in sample preparation, along with the rapid and reliable technique of GCMS would give significant contribution in running fast, auto¬ mated analysis in validation of animal oil samples for Halal authentication purposes.